Multimodal Video-Feedback: A Promising way of Giving Feedback on Student Research - Froehlich, Dominik Emanuel; Guias, Dorothea (Frontiers in Education, 2021)
Feedback is a valuable pedagogical tool to guide students through research projects and aid the acquisition of methodological knowledge. However, its potential is rarely exhausted. In this article, we describe one digital pedagogical solution to improve feedback practices in higher education: multimodal video-feedback. After showing the conceptually different process and outcomes of this technique relative to more traditional ways of giving feedback, we provide first empirical quantitative and qualitative evidence about its usefulness based on 77 course evaluations. We then discuss avenues for further research and how the practice itself could be developed and tailored to the specific needs to individual lecturers.